2015
DOI: 10.1016/j.ijplas.2014.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of localized necking in substrate-supported metal layers: Comparison of bifurcation and imperfection analyses

Abstract: a b s t r a c tLocalized necking is often considered as precursor to failure in metal components. In modern technologies, functional components (e.g., in flexible electronic devices) may be affected by this necking phenomenon, and to avoid the occurrence of strain localization, elastomer substrates are bonded to the metal layers. This paper proposes an investigation of the development of localized necking in both freestanding metal layers and elastomer/ metal bilayers. Finite strain versions of both rigid-plas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
34
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 37 publications
(47 citation statements)
references
References 37 publications
13
34
0
Order By: Relevance
“…However, for positive strain paths ( 0 r > ), the trend is completely different for the RSL framework, in which the determinant decreases very slightly for 0.1 r = and keeps practically a constant value for 1 r = or 0.5 r = . As discussed in the literature, most often within phenomenological constitutive frameworks (see, e.g., Rice, 1976;Hutchinson and Neale, 1978;Ben Bettaieb and Abed-Meraim, 2015), it is found that when the shearing components of the tangent modulus keep their high elastic values, the use of bifurcation theory as localization criterion yields unrealistically high localization strains in the positive biaxial stretching range. Here, the localization predictions suggest values for the critical strains far beyond 2.…”
Section: Numerical Results At the Macroscalementioning
confidence: 99%
See 1 more Smart Citation
“…However, for positive strain paths ( 0 r > ), the trend is completely different for the RSL framework, in which the determinant decreases very slightly for 0.1 r = and keeps practically a constant value for 1 r = or 0.5 r = . As discussed in the literature, most often within phenomenological constitutive frameworks (see, e.g., Rice, 1976;Hutchinson and Neale, 1978;Ben Bettaieb and Abed-Meraim, 2015), it is found that when the shearing components of the tangent modulus keep their high elastic values, the use of bifurcation theory as localization criterion yields unrealistically high localization strains in the positive biaxial stretching range. Here, the localization predictions suggest values for the critical strains far beyond 2.…”
Section: Numerical Results At the Macroscalementioning
confidence: 99%
“…As discussed above, the application of the bifurcation approach leads to unrealistically high limit strains in the right-hand side of the FLD, when the flow theory with associative plasticity and smooth yield surface is used (Rice, 1976;Ben Bettaieb and Abed-Meraim, 2015). In the framework of micromechanical modeling, based on crystal plasticity, one can wonder how realistic the predicted FLDs would be if a rounded yield surface is used instead of the sharper yield surface associated with the classical Schmid law.…”
Section: Introductionmentioning
confidence: 99%
“…For each loading (determined by a strain path and a band orientation), the computations are stopped when the norm of the jump vector PS PS C increases rapidly, thus marking the localization of the deformation in the band zone. Further numerical and algorithmic details regarding the M-K approach can be found in [7].…”
Section: Numiform 2016mentioning
confidence: 99%
“…The current paper may be viewed as an extension of the investigations carried out in [7], which were restricted to a phenomenological description for the mechanical behavior of the metal layer.…”
Section: Introductionmentioning
confidence: 99%
“…These numerical tools have been originally developed in [14] and recently revisited and improved in [15] . In these tools, two main strain localization criteria have been used to predict the occurrence of localized necking: the bifurcation theory and the Marciniak and Kuczynski approach (also referred to as the initial imperfection approach).…”
Section: Introductionmentioning
confidence: 99%